Still Lifes. Notes on withering refuge and beyond - Neto, Pedro Figueiredo (2023)
Withering Refuge (2020) is a film-article that explores visual representations of displacement and the possibilities of refuge amidst environmental decline, developmental and extractive endeavours, in and around Meheba Refugee Camp, Zambia. This article interrogates the tropes of still life artworks as it displays a collection of film stills from Withering Refuge. Selected images not only dialogue with the temporal, spatial and social stillness often depicted in still lifes and described in the forced migration literature as, drawing on the Latin version of still life (nature morte), the piece ultimately invites readers-viewers to reflect on the current situation in the region and the uncertain prospects for those seeking refuge writ large.